Effect of Copper Treatment on the Composition and Function of the Bacterial Community in the Sponge Haliclona cymaeformis - Ren-Mao Tian (American Society for Microbiology, 2014)
ABSTRACT Marine sponges are the most primitive metazoan and host symbiotic microorganisms. They are crucial components of the marine ecological system and play an essential role in pelagic processes. Copper pollution is currently a widespread problem and poses a threat to marine organisms. Here, we examined the effects of copper treatment on the composition of the sponge-associated bacterial community and the genetic features that facilitate the survival of enriched bacteria under copper stress. The 16S rRNA gene sequencing results showed that the sponge Haliclona cymaeformis harbored symbiotic sulfur-oxidizing Ectothiorhodospiraceae and photosynthetic Cyanobacteria as dominant species. However, these autotrophic bacteria decreased substantially after treatment with a high copper concentration, which enriched for a heterotrophic-bacterium-dominated community. Metagenomic comparison revealed a varied profile of functional genes and enriched functions, including bacterial motility and chemotaxis, extracellular polysaccharide and capsule synthesis, virulence-associated genes, and genes involved in cell signaling and regulation, suggesting short-period mechanisms of the enriched bacterial community for surviving copper stress in the microenvironment of the sponge. Microscopic observation and comparison revealed dynamic bacterial aggregation within the matrix and lysis of sponge cells. The bacteriophage community was also enriched, and the complete genome of a dominant phage was determined, implying that a lytic phage cycle was stimulated by the high copper concentration. This study demonstrated a copper-induced shift in the composition of functional genes of the sponge-associated bacterial community, revealing the selective effect of copper treatment on the functions of the bacterial community in the microenvironment of the sponge. IMPORTANCE This study determined the bacterial community structure of the common sponge Haliclona cymaeformis and examined the effect of copper treatment on the community structure and functional gene composition, revealing that copper treatment had a selective effect on the functions of the bacterial community in the sponge. These findings suggest that copper pollution has an ecological impact on the sponge symbiont. The analysis showed that the untreated sponges hosted symbiotic autotrophic bacteria as dominant species, and the high-concentration copper treatment enriched for a heterotrophic bacterial community with enrichment for genes important for bacterial motility, supplementary cellular components, signaling and regulation, and virulence. Microscopic observation showed obvious bacterial aggregation and a reduction of sponge cell numbers in treated sponges, which suggested the formation of aggregates to reduce the copper concentration. The enrichment for functions of directional bacterial movement and supplementary cellular components and the formation of bacterial aggregates and phage enrichment are novel findings in sponge studies.